Data from: A full annual perspective on sex-biased migration timing in long-distance migratory birds ... - Briedis, Martins; Bauer, Silke; Adamik, Peter; Alves, José A.; Costa, Joana S.; Emmenegger, Tamara; Gustafsson, Lars; Koleček, Jaroslav; Liechti, Felix; Meier, Christoph M.; Prochazka, Petr; Hahn, Steffen (Dryad, 2019)
In many taxa, the most common form of sex-biased migration timing is protandry – the earlier arrival of males at breeding areas. Here we test this concept across the annual cycle of long-distance migratory birds. Using more than 350 migration tracks of small-bodied trans-Saharan migrants, we quantify differences in male and female migration schedules and test for proximate determinants of sex-specific timing. In spring, males on average departed from the African non-breeding sites about 3 days earlier and reached breeding sites ca. 4 days ahead of females. In autumn, males started migration about 2 days earlier, but this difference did not carry-over to arrival at the non-breeding sites. A cross-species comparison revealed large variation in the level of protandry and protogyny across the annual cycle. While we found tight links between individual timing of departure and arrival within each migration season, only for males the timing of spring migration was linked to the timing of previous autumn migration. ... : Sex-biased migration timing in 14 Afro-Palearctic migratory birdsdatabase_submission.csv ...